Study of a Falling Rigid Particle Passing Around Obstacles in a Fluid Channel. Issue 9 (20th October 2020) - Usman, Kamran; Ali, Jabbar; Mahmood, Rashid; Bilal, Sardar; Jabeen, Saqia; Asmat, Junaid
Abstract : We have examined the effects on fluid and particle motion due to solid particles passing around circular obstacles in particulate flows. Particle interaction with internal obstacles, outer boundary and with the fluid is inspected. Eulerian approach using a fixed computational mesh is used across which the solid particles move freely in fluid. Treatment of fluid and particle interaction inside the whole domain is carried using Fictitious boundary method. A modified collision model is presented to handle particle-cylinder interactions. The particulate flow is computed using multigrid finite element solver FEATFLOW. Numerical experiments are performed considering different particle positions and different alignment of cylinders (obstacles). Effects on the motion of the particle and on the physical behaviour of the fluid-particle system due to the particle-wall, particle-cylinder and particle-fluid interactions has been analysed.